Rationale, design, and baseline characteristics of the Cardiovascular Prognostic COUPLING Study in Japan (the COUPLING Registry). Issue 3 (24th February 2020) - Kario, Kazuomi; Kabutoya, Tomoyuki; Fujiwara, Takeshi; Negishi, Keita; Nishizawa, Masafumi; Yamamoto, Mitsuyoshi; Yamagiwa, Kayo; Kawashima, Akihiro; Yoshida, Tetsuro; Nakazato, Jun; Matsui, Yoshio; Sekizuka, Hiromitsu; et al.
Abstract: Vascular biomarkers, including the cardio‐ankle vascular index (CAVI), are increasingly being recognized as important indicators of cardiovascular risk. CAVI has been shown to have good discriminative ability for detecting new‐onset hypertension, but results of studies investigating cardiovascular risk prediction are inconsistent. Furthermore, there is a lack of data on the prognostic value of changes in CAVI over time. The Cardiovascular Prognostic Coupling study was designed to determine the impact of baseline CAVI and changes in CAVI on cardiovascular events in a Japanese cohort. The design of the ongoing, multicenter, prospective, observational registry and baseline characteristics of the enrolled population are reported. Eligible consecutive patients were aged ≥30 years, had ≥1 cardiovascular risk factor, and were being treated according to relevant Japanese guidelines. The primary outcome is time to onset of a major cardiovascular event (a composite of cerebral infarction, cerebral hemorrhage, subarachnoid hemorrhage, stroke of unknown etiology, myocardial infarction, cardiovascular intervention for angina pectoris, and sudden death). Screening and enrollment occurred over a period of 3 years, followed by ≥7 years of follow‐up, with CAVI determined annually. A total of 5279 patients were registered, of whom 5109 had baseline data available and will be included in future analyses. Mean CAVI at baseline was 8.8 ± 1.4. The proportion of patients with CAVI of <8, 8‐10 or >10 was 25.3%, 57.0%, and 17.7%, respectively. Data from this registry should provide information on the significance of baseline CAVI and change in CAVI as indicators of cardiovascular prognosis in a representative patient population.